2009
DOI: 10.1089/cbr.2008.0552
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Melanoma Therapy by Chemotherapy and Autoimmunity Induced by Cytokine

Abstract: The combination of DTIC with GM-CSF and IL-2 is feasible and possibly efficacious for clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Clinical efficacy in studies varied widely, with response rates ranging from no response to >40% [53-58]. It is worth noting that several of the studies reporting high overall response rates also reported significant increases in T-cell, DC, macrophage, or natural killer–cell populations following treatment [53,55,58]. One study evaluating a chemotherapy regimen of dacarbazine, interferon-α2b, interleukin-2, and tamoxifen with three doses of GM-CSF reported a dose–response effect with increasing exposure to GM-CSF via administration over a greater number of days ( P  = 0.016) [59].…”
Section: Reviewmentioning
confidence: 99%
“…Clinical efficacy in studies varied widely, with response rates ranging from no response to >40% [53-58]. It is worth noting that several of the studies reporting high overall response rates also reported significant increases in T-cell, DC, macrophage, or natural killer–cell populations following treatment [53,55,58]. One study evaluating a chemotherapy regimen of dacarbazine, interferon-α2b, interleukin-2, and tamoxifen with three doses of GM-CSF reported a dose–response effect with increasing exposure to GM-CSF via administration over a greater number of days ( P  = 0.016) [59].…”
Section: Reviewmentioning
confidence: 99%
“…Autoimmunity is generally recognized as a possible severe side effect of melanoma therapy, upon interferon- [ 22 ] or ipilimumab-treatment [ 23 ]. On the other hand, unchaining the immune system is the main goal of current immunotherapy protocols as well as previous approaches combining dacarbazine with IL-2 and GM-CSF [ 24 ]. Data published in 2018 indicate a high prevalence rate of pre-existing autoimmune comorbidities in melanoma patients as compared to the general population (28.3% and 19.8% in metastatic and not-metastatic melanoma, respectively, as compared to 9.2% in the general population) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%